Thermo-electric effects in a Luttinger liquid: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Krive, I. V.; Romanovsky, I. A.; Bogachek, E. N.; Scherbakov, A. G.; Landman, Uzi (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Thermoelectric effects in a Luttinger liquid (LL) wire adiabatically connected to the leads of noninteracting electrons are considered. For a multichannel LL a staircase-like behavior of the thermalconductance as a function of chemical potential is found. A thermopower for a LL wire with an impurity is evaluated for two cases: (i) LL constriction and (ii) infinite LL wire. We show that the thermopower is described a Mott-like formula renormalized by an interaction-dependent factor. For an infinite LL therenormalization factor decreases with increase of the interaction. However, for a realistic situation, when a LL wire is connected to the leads of noninteracting electrons (LL constriction), the repulsiveelectron-electron interaction enhances the thermopower. A nonlinear Peltier effect in a LL is briefly discussed.